The Role Of Green HRM In Talent Management Development To Improve Employee Performance In Hospitality Companies - Dyah Palupiningtyas; Retno Mulatsih; Sulistyowati; Andar Sri Sumantri (Pusat Riset dan Inovasi Nasional, 2024)
This qualitative study examines the role of green human resource management (HRM) in talent management development to improve employee performance in hospitality companies. Data was collected through interviews with hospitality company managers and analyzed using thematic analysis. The background establishes the importance of environmental sustainability in the hospitality industry and the emergence of green HRM. The results demonstrate that green HRM practices like sustainability training, rewards for green behaviors, and recruiting environmentally-conscious employees enable hospitality companies to attract and retain talented employees, developing their skills to drive guest satisfaction and financial performance.